A credible past and a shameless body: history, violence and repetition in the lives of asylum seekers women in Italy - Taliani, Simona (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2011)
This article examines the traumatic experiences of female asylum seekers in Italy, primarily from the Democratic Republic of Congo, Ivory Coast, and Ethiopia. Through clinical and ethnographic research conducted at the Frantz Fanon Center in Turin, the author analyzes the complex relationships between violence, memory, and repetition in their biographies. Drawing on psychoanalytic and anthropological concepts, the study questions how social institutions create "victims" and how these women construct themselves as such. The article also explores the challenges of care practices and legal recognition of trauma within the European context. Un passé crédible et un corps sans honte : histoire, violence et répétition dans les parcours de femmes demandeuses d’asile en Italie Cet article explore les expériences traumatiques des femmes demandeuses d'asile en Italie, principalement originaires de la République Démocratique du Congo, de la Côte d'Ivoire et d'Éthiopie. À travers une recherche clinique et ethnographique menée au Centre Frantz Fanon de Turin, l'auteure analyse les liens complexes entre violence, mémoire et répétition dans leurs biographies. En s'appuyant sur des concepts psychanalytiques et anthropologiques, l'étude interroge la manière dont les institutions sociales produisent des "victimes" et comment ces femmes se construisent elles-mêmes en tant que telles. L'article examine également les implications des pratiques de prise en charge et de reconnaissance juridique des traumatismes dans le contexte européen.